Phenotypic Restoration by Molybdate of Nitrate Reductase Activity in chlD Mutants of Escherichia coli - Glaser, J. H. (1971)
ChlD mutants of Escherichia coli are pleiotropic, lacking formate-nitrate reductase activity as well as formate-hydrogenlyase activity. Whole-chain formate-nitrate reductase activity, assayed with formate as the electron donor and measuring the amount of nitrite produced, was restored to wild-type levels in the mutants by addition of 10(−4)m molybdate to the growth medium. Under these conditions, the activity of each of the components of the membrane-bound nitrate reductase chain increased after molybdate supplementation. In the absence of nitrate, the activities of the formate-hydrogenlyase system were also restored by molybdate. Strains deleted for the chlD gene responded in a similar way to molybdate supplementation. The concentration of molybdenum in the chlD mutant cells did not differ significantly from that in the wild-type cells at either low or high concentrations of molybdate in the medium. However, the distribution of molybdenum between the soluble protein and membrane fractions differed significantly from wild type. We conclude that the chlD gene product cannot be a structural component of the formate-hydrogenlyase pathway or the formate-nitrate reductase pathway, but that it must have an indirect role in processing molybdate to a form necessary for both electron transport systems.